Identification of an Immune-Related Gene Signature to Improve Prognosis Prediction in Colorectal Cancer Patients - Dai, Siqi; Xu, Shuang; Ye, Yao; Ding, Kefeng (Frontiers in Genetics, 2020)
Background. Despite recent advance in immune therapy, great heterogeneity exists in colorectal cancer (CRC) patients’ outcome. In this study, we aimed to analyze the Immune-related gene (IRG) expression profiles from two independent public databases and develop an effective signature to forecast patients’ prognosis. Method. IRGs were collected from The Cancer Genome Atlas (TCGA) database to identify a prognostic genes signature, which was verified in Gene Expression Omnibus (GEO) database. Gene function enrichment and immune cell infiltration analyses were conducted. A prognostic nomogram was built incorporating the IRG signature with clinical risk factors. Results. The training and test datasets had 487 and 579 patients, respectively. A prognostic six-gene-signature (CCL22, LIMK1, MAPKAPK3, FLOT1, GPRC5B and IL20RB) was developed through feature selection, and yielded incredible differentiation between low and high-risk group in the training set (P < 0.001), which was confirmed in the test group (P < 0.001). The signature outperformed tumor staging regarding survival prediction. Go and KEGG functional annotation analysis suggested the signature were significantly enriched in metabolic process and regulation of immunity (P<0.05). When combined with clinical risk factors, the model showed robust prediction capability. Conclusion. The immune-related six-gene signature is a reliable prognostic indicator for CRC patients and could bring insight for personalized cancer management.